DAMPAK ZAKAT TERHADAP PEREKONOMIAN - Harfandi, Harfandi (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2008)
Zakah is an obligation's of the people of Islam and represent a comitment a Moslem in the field of economic social. Zakah can protect the society from of the social disaster like poornes, weakness of physical and also the sprit of life. The institute of zakah is the medium of properties distribution in Islamic world, the repsenting the clloective obligation of Moslem. Refering to this relegius obligatory (zakah), it has impact to hte following aspect in economic; 1) zakah can improve and repair currency function, 2) zakah can develop the money or properties, 3) zakah can increase the averall production in economics, 4) zakah can improve earning of society.